Symbolic compliance or substantive transparency? Sustainability reporting, corporate attributes, and financial reporting quality in Indonesia - Almalita, Yuliani; Almaida Dwi Kusuma (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study investigates the effect of sustainability reporting on financial reporting quality in Indonesian manufacturing companies during 2022–2024. Using 375 firm-year observations from 125 listed firms, this study applies panel data regression with the Random Effects Model (REM). The results show that sustainability reporting, sustainability reporting quality, and audit quality do not significantly influence financial reporting quality. In contrast, revenue growth and leverage negatively affect financial reporting quality, whereas firm size and tangibility positively influence reporting quality. These findings indicate that firms’ financial characteristics play a more substantial role in determining reporting quality than sustainability disclosure practices. This study contributes to sustainability accounting literature by providing evidence from an emerging market context. Future research should examine governance mechanisms, ESG assurance, and industry-specific factors to better explain variations in financial reporting quality.